Efeito da cobertura sobre o desenvolvimento do cedro-rosa (Cedrela fissilis) e nos danos causados por Hypsipyla grandella em sistema agroflorestal - Borges, Rafael; Boff, Mari Inês Carissimi; Blassioni-Moraes, Maria Carolina; Biscaro-Borges, Camila; Mantovani, Adelar (Ciência Florestal, 2019)
Cedrela fissilis (Vell.) is an important wood species, native to South America. It is appreciated for its physical characteristics and, therefore, its native specimens are overexploited.Commercial cultivation initiatives have been continuously flawed as a result of the damage caused by mahogany shoot borer Hypsipyla grandella (Zeller, 1848).Planting under shaded sites has been one of the management methods used to reduce insect attacks. However, the reason why mahogany shoot borer does not attack shaded plants as often is still unknown. Therefore, the aim of this research was to find cultivation parameters that could combine proper plant development and low rate ofattacks by Hypsipyla grandella.For this purpose, increases in height and shoot diameter of cedar seedlings, planted in agroforestry systems, were monitored for the two first years. Three canopy cover rates, namely, 0-20%, 20-40% and 40-60%, were tested for plant development andfrequency of attacks byHypsipyla grandella. The adult population of the insect was monitored with semiochemicals throughout the experimental period, and two pheromonal blends and one food bait were tested. Field results showed that one of the pheromone blends was efficient in identifying small variations in the population of adult specimens. Regarding to the plant development, the treatment with the highest cover rate showed the lowest parameters compared to the intermediate cover. The frequency of attacks byHypsipyla grandella was greater in the treatment with the lowest cover (0-20%).The results suggest that in canopy cover, ranging from 20 to 40%, good rates of initial development of plants can be combined with low frequency of attack by Hypsipyla grandella.